Non-sputum-based triage and confirmatory diagnostic tests for pediatric TB - A. Drane; A. Molkenthin; M. Gassama; S. Pouzol; P. Vanhems; J. Hoffmann (IJTLD Open)
BACKGROUND: Non-sputum-based triage and confirmatory tests are essential for early TB detection and timely treatment in children. METHODS: A mini-review was conducted from January 2022 to May 2024, evaluating five studies on non-sputum-based assays for childhood TB diagnosis. Both Microbiological and Clinical Reference Standards were used to assess diagnostic accuracy and triage potential. RESULTS: Among the confirmatory tests, only the gastric aspiration test with cartridge-based nucleic acid amplification tests (CBNAAT) met the WHO Target Product Profile criteria. However, this method remains invasive and is not suitable for point-of-care testing. Urine testing by gas chromatography–mass spectrometry (GC/MS) or C-ELISA (BJ76/A194) demonstrated high performance but lacked point-of-care applicability in resource-limited settings. Stool testing with CBNAAT is a viable alternative with high specificity but low sensitivity. For triage, urine lipoarabinomannan tests and blood MTB-HR tests show promise based on specificity, practicality, cost, and turnaround time. CONCLUSION: This review highlights the performance of non-sputum-based assays for childhood TB and their potential as triage tools. While some other innovations show promise for the triage and/or diagnosis of TB in adults, further studies are needed to evaluate the performance of these tests in pediatric populations.